2012
DOI: 10.1007/s00586-012-2157-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multilevel anterior cervical fusion on neck motion

Abstract: Background Anterior cervical decompression and fusion (ACDF) procedures are successful in treating multilevel cervical radiculopathy and cervical myelopathy. It was reported that this procedure would result in a loss of cervical range of motion. However, few studies have focused on the exact impact of multilevel (more than 3 levels) ACDF on cervical range of motion. Methods 29 patients underwent a 3-level or 4-level ACDF. In all the patients, preoperative active cervical ROM measurement was performed, and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…In the biomechanics research, Prasarn et al [28] found that the range of motion of adjacent segments increased significantly on the double segments fusion. Wu XD et al [29] found that more than three segments had a significant effect on the cervical range of motion. The reason could be that with the increasing of the number of fusion segments, the activity of the upper adjacent segment and the small joint pressure gradually increase, resulting in the acceleration of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In the biomechanics research, Prasarn et al [28] found that the range of motion of adjacent segments increased significantly on the double segments fusion. Wu XD et al [29] found that more than three segments had a significant effect on the cervical range of motion. The reason could be that with the increasing of the number of fusion segments, the activity of the upper adjacent segment and the small joint pressure gradually increase, resulting in the acceleration of ASD.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 3 4 5 Despite the proven long-term clinical and radiographic success, ACDF is associated with certain disadvantages, including the loss of motion segments, the potential for accelerated adjacent segment disease, and the reliance on the need for solid bony fusion. 6 7 8 9 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…Internal instrumentation has undergone significant developments since this report; as such, one may expect a decrease in the use of bracing due to the known restriction of neck motion after multilevel fusion. 35 The paucity of Abbreviations: LOS, length of stay; QALY, quality-adjusted life year; SD, standard deviation. decisive literature has made it challenging to make an informed decision about bracing in the setting of multilevel ACDF.…”
Section: Discussionmentioning
confidence: 99%